The Determinants of Visitor’s Revisit Intention: A Lesson from Ijen Car Free Day - Cesya Rizkika Parahiyanti; Ananda Sabil Hussein (Department of Management, Faculty of Economics and Business, Brawijaya University, 2014)
Event industry currently is considered as one of interesting business opportunity in contributing major positive economic impact. Event could be categorized into some activities conducted by an event management or event organizer in the case of achieving some specific outcomes. An event is also recognized as an essential marketing tool in branding of particular destination. It has a powerful function to make a differentiation between one destination and others. This study aims to establish a theoretical event brand equity for which the key components of the brand equity were evaluated from visitor perspective in the tourism context. Brand equity is constructed by four multidimensions which are event brand awareness (EBA), event brand image (EBI), event brand quality (EBQ), and event revisit intention (ERI). By using convenience sampling, 205 visitors of Ijen Car Free Day (ICFD) as the event object were used as respondents to obtain the data. This study uses Partial Least Square (PLS) to analyze the data both in outer model and inner model measurements. The finding of this study indicate that EBA has positive and significant influence to EBI, EBQ, and ERI. Then, EBI is also proven giving positive and significant influence to EBQ and ERI. In contrary, EBQ does not show significant influence to ERI. The significance movement of this study could be useful measurement in assessing event brand equity management in the future.